The Impact of Fintech Application on the profitability of the banking sector in Algeria: An analytical and Statistical Econometric Study for Period (2010-2022) [In Arabic] - Benzeid, Rabia; Kadja, Amina; Ammeni, Lamia (Finance and Business Economies Review, 2022)
This study aims to detect the impact of the application of financial technology services, represented by the number of automated teller machines (ATMs) per 100,000 adults and the number of interbank payment cards (CIB) issued in Algeria, on the profitability of the Algerian banking sector as measured by the rate of return on equity (ROE) for annual data during the period (2010-2019), using a multiple linear regression model. This was preceded by a statistical study of the reality of the application of financial technology services in Algeria during the period (2016-May 2022). The study found a positive significant effect of the two indicators of financial technology on the rate of return on equity (ROE). In order to benefit the banking sector in Algeria from the advantages of financial technology the concerned authorities should pay attention to the need to develop the banking sector and provide technical infrastructure and appropriate financial technology services.